Influence of subsidies and promotional strategies on outcomes in a beneficiary‐based commercial weight‐loss programme. Issue 3 (7th April 2019) - Gudzune, Kimberly A.; Alexander, Eleanore; Tseng, Eva; Durkin, Nowella; Jerome, Gerald J.; Dalcin, Arlene; Appel, Lawrence J.; Clark, Jeanne M.
Abstract : To determine whether initial engagement, continued participation, and weight loss vary by subsidy and promotional strategies in a beneficiary‐based, commercial weight‐loss programme. We conducted a retrospective analysis of data from 2013 to 2016. Our dependent variables included initial engagement (≥1 calls; ≥2 weights), coach calls and weight change. Our independent variables were subsidy strategy (total subsidy (n = 9) vs cost sharing (n = 3)) and combination of promotional‐subsidy strategies (mixed campaign + total subsidy (n = 6) vs mass media + total subsidy (n = 3)). We used logistic and linear regression analyses adjusted for beneficiary factors and clustering by organization. From 12 participating organizations, 26 068 beneficiaries registered of which 6215 initially engaged. Cost sharing was associated with significantly greater initial engagement as compared to total subsidy (OR 3.73, P < 0.001); however, no significant between‐group differences existed in calls or weight change. Mass media + total subsidy group had significantly greater calls and weight loss at 12 months compared to mixed campaign + total subsidy (−2.6% vs −1.8%, P = 0.04). Cost sharing may promote greater initial engagement, although does not contribute to better participation or weight loss relative to total subsidy. If organizations elect total subsidy, then pairing this strategy with a mass media campaign may promote greater participation and weight loss among beneficiaries.